The Influence of using the Quizizz Application on the Interest in Learning History Among XI IPS Students at SMAN 1 Alalak - Ridhani, M. Taufik; Putro, Herry Porda Nugroho; Sriwati, Sriwati (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
In the 21st century, rapid technological development has led to various new innovations, especially in educational media. This requires teachers to be able to use various types of educational media as a result of technological advancements. Quizizz can be a solution for teachers to utilize existing technology, making the learning process more engaging. The research method used in this study is a quantitative experimental method. The data collection technique used is a questionnaire. The data analysis method uses the Independent t-test. From the data analysis results using IBM SPSS version 25, it was found that there is a difference in the average post-test scores between the experimental class and the control class with a significance value (2-tailed) of 0.001. Therefore, it can be concluded that H1 is accepted and H0 is rejected. This indicates that the use of Quizizz as a learning medium has an impact on students' interest in learning History at SMAN 1 Alalak.